Students’ Knowledge Profile of Sasambo Medicinal Oil in the Phytochemistry Course - Listantia, Nora; Jufri, A. Wahab; Gunawan, Erin Ryantin; Gunawan, Gunawan; Rokhmat, Joni; Sukarso, A. A. (Jurnal Biologi Tropis, 2025)
Sasambo Medicinal Oil is a local wisdom–based product from West Nusa Tenggara (NTB) that utilizes medicinal plants such as lemongrass, ginger, turmeric, eucalyptus, and various other ethnopharmaceutical species. In the context of phytochemistry learning, the use of this oil serves as a relevant medium for connecting the concept of secondary metabolites with the practical application of natural-product utilization. This study aims to describe the knowledge profile of students regarding Sasambo medicinal oil as a cultural heritage product that possesses significant phytochemical potential and economic value, as well as its contribution to enhancing scientific literacy. Students’ understanding of the components, benefits, and preparation processes of this traditional medicinal oil is essential to develop within chemistry education based on local wisdom. The research employed a descriptive quantitative method using closed-ended questionnaires and interviews as instruments. The research subjects consisted of 52 students from the Chemistry Education Study Program at the University of Mataram. The findings show that 73% of students have general knowledge about Sasambo oil, yet only 38% understand its chemical composition and pharmacological mechanisms. Students’ conceptual and procedural knowledge falls within the moderate category (average score of 65.2%), while the applicative aspect remains low (54.1%). These results indicate the need to strengthen scientific literacy and integrate local wisdom into applied chemistry and phytochemistry learning, thereby improving students’ conceptual understanding and awareness of the scientific and sustainable utilization of natural resources.